Trade and Women's Economic Empowerment Evidence from Small and Medium-Sized Enterprises - Samy, Yiagadeesen (Springer Nature, 2023)
This open access book examines the relationship between trade and women's economic empowerment by focusing on small and medium enterprises (SMEs) in six countries: Cambodia, Ghana, Madagascar, Nigeria, Senegal and Vietnam. The authors make use of both survey data and qualitative analysis to understand why and how trade can create more jobs for women, and how the jobs created are contributing to women's empowerment. They propose strategies and policies for ensuring that women can benefit from trade. After providing the context for the research and reviewing the literature on trade and gender in the introductory chapter, the second chapter analyzes survey data collected for this project. This is followed by a qualitative analysis of the six country cases in the next two chapters: Cambodia and Vietnam (Chapter 3), followed by Ghana, Madagascar, Nigeria and Senegal (Chapter 4). The final chapter concludes with a summary of our findings and policy recommendations.